2015
DOI: 10.1016/j.jss.2015.03.099
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating visual perception for assessing reconstructed flap health

Abstract: Background Detecting failing tissue flaps before they are clinically apparent has the potential to improve post-operative flap management and salvage rates. This study demonstrates a model to quantitatively compare clinical appearance, as recorded via digital camera, with spatial frequency domain imaging (SFDI), a non-invasive imaging technique utilizing patterned illumination to generate images of total hemoglobin and tissue oxygen saturation. Methods Using a swine pedicle model where blood flow was careful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similarly, hyperspectral imaging uses wavelengths between 500 and 700 nm to provide information on oxygenated haemoglobin (HbO 2 ) and deoxygenated haemoglobin (Hb) in burn and diabetic wounds, creating anatomical tissue StO 2 maps that may predict the risk of ulceration in the diabetic foot before it occurs . In our case, we use spatial frequency domain imaging (SFDI), which has been used to examine reconstructive surgery, port wine stain response to therapy, and burn wound severity assessment . In this study, SFDI was used to evaluate the macroscopic changes in HbO 2 , Hb, and StO 2 within wounds in normal versus streptozotocin (STZ) diabetic animals and then combining this observation with NF‐κB and iNOS expression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, hyperspectral imaging uses wavelengths between 500 and 700 nm to provide information on oxygenated haemoglobin (HbO 2 ) and deoxygenated haemoglobin (Hb) in burn and diabetic wounds, creating anatomical tissue StO 2 maps that may predict the risk of ulceration in the diabetic foot before it occurs . In our case, we use spatial frequency domain imaging (SFDI), which has been used to examine reconstructive surgery, port wine stain response to therapy, and burn wound severity assessment . In this study, SFDI was used to evaluate the macroscopic changes in HbO 2 , Hb, and StO 2 within wounds in normal versus streptozotocin (STZ) diabetic animals and then combining this observation with NF‐κB and iNOS expression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…14 Following this work, further studies demonstrated that SFDI could detect partial changes in flap circulation (50% blockage) prior to measurable changes in visual color. 104 Confirming the diagnostic potential of SFDI, additional work demonstrated that severe ischemic conditions measured by SFDI in a cutaneous pedicle flaps was predictive of necrosis. 101 Beyond the diagnostic potential of oxygenation imaging, it was also demonstrated that the source of the occlusion (arterial versus venous) could be identified as early as 2 min after blockage in a hemifacial composite flap transplants.…”
Section: Surgical Guidancementioning
confidence: 89%
“…Similar models have since been studied in animals to validate the utility of SFDI evaluation of flap profusion and viability 105 107 While skin flap viability is classically assessed by visual inspection, SFDI has shown promise in detecting profusion changes before they are perceptible to the eye by tracking vascular parameters such as total hemoglobin concentration and oxygen saturation 108 …”
Section: Spatial Frequency-domain Imagingmentioning
confidence: 99%